GROUNDWATER MONITORING FOR CEMENT KILN DUST DISPOSAL UNITS IN KARST AQUIFERS - Zhou W.; Beck B.F.; Wang J.; Pettit A.J. (My University, 2007)
Well-developed karst aquifers tend to be heterogeneous and consist of variable porosities. Groundwater monitoring and the associated data interpretations in such aquifers are often more complicated than porous medium aquifers. Collection of representative data in karst aquifers often requires monitoring at appropriately located wells and/or springs that are proven to connect to the groundwater system. Water samples are to be collected under different flow conditions, including base flow, high-flow, and low-flow. The sampling frequencies may vary from several months for base flows to minutes in response to recharge events. The groundwater monitoring program presented in this paper is for a cement kiln dust mono-fill site in a karst area of southern Indiana. Following dye tracing and extensive geophysical investigations, one spring was selected as a monitoring location. A second spring should be used as a monitoring location when the last cell of the mono-fill begins receiving the wastes. The paper discusses results from the first spring, at which nine background sampling events were completed to evaluate the natural variations of the water quality. Based on the background data, a statistical evaluation plan was developed for 12 water-quality parameters to determine the integrity of the landfill. The statistical power of the statistical analyses was evaluated by Monte Carlo simulations.
Keywords: KARST; LANDFILL; GROUNDWATER MONITORING; SAMPLING AND ANALYSIS PLAN; STATISTICAL EVALUATION PLAN